A comparison of anxiety sensitivity and emotion regulation between substance abusers and healthy people - P Dabaghi; S Fahimi; A Taghva; M Rahimkhanli (فصلنامه ابن سینا)
Background: We can obtain important information about the treatment of addictive behaviors by understanding the underlying causes of substance abuse disorders such as anxiety sensitivity and emotion regulation strategies. The aim of our present study was to compare anxiety sensitivity and emotion regulation between substance dependent Individuals and healthy population.